Institutional And Regulatory Failures - Obstacles to PV Electricity Prosuming Households in Bulgaria - Svetlana GERCHEVA (Communications of International Proceedings, 2022)
There is a huge potential for clean power production from solar energy. The current paper focuses on some impediments to electricity household prosumption in Bulgaria. In particular, it zooms in on several controversial, ill-conceived or delayed energy regulations as well some institutional failures to enforce the latter in order to increase photovoltaic technology adoption among families. Using the desk research method, we search within the public registry of the Bulgarian Agency for Sustainable Energy Development, studying the newly installed household PV projects in terms of their diffusion, capacity installed and location across the country and throughout the period after the Act on renewable energy was adopted back in 2011. Having conducted a detailed analysis, some measures have been identified and discussed in order to eliminate regulatory and institutional bottlenecks, which would benefit the household electricity prosumption in Bulgaria.
Keywords: electricity prosumption; households in Bulgaria; energy sector regulations; institutional and regulatory failures